Atlas al Hadarah al lslamiyah - Riad Nourallah (International Institute of Islamic Thought, 1999)
Atlas was first published in its original English edition in 1986. The collaboration of Temple University, the International Institute of Islamic Thought (IIIT), and the American Trust Publications with Macmillan made the publication possible. At the time, the book clearly marked a qualitative leap in terms of writings on Islamic culture and civilization. With its large format, over 500 pages, and hundreds of maps, tables, charts, chronologies, photographs, and illustrations, it sought to catch the eyes (and minds) of a wide range of readers, sacrificing little in the way of erudition or pertinent detail and shunning both geographical and chronological arrangements. These two approaches, the authors pointed out, would have been unsuitable for such a work, seeking to highlight the “essence” of the Muslim experience in the midst of and despite the bewildering diversity of that experience. Nor was the new venture merely a blend of the two methods with their perceived “shortcomings,” but one which followed the “phenomenological” method, where “the observer let[s] the phenomena speak for themselves rather than force them into any predetermined ideational framework.” The Faruqis saw themselves as innovators in applying this method (traced to Edmund Husserl and Max Scheler) to the study of Islam. The method was advantageous as it allowed them to escape both the “epistemological ethnocentrism” of Western Islamicists and the “uncritical” assumptions of Muslim scholars. In the tradition of other Muslim harmonizers, and with a mix of genuine humility and some unconscious trepidation, they also stressed that their work was “a beginning.” Surely Atlas was no starting point for the Faruqis. For many years they had worked together, or individually, on many a project, book, and seminar - papers on music, compendiums on world and Asian religions, books on Islam, symposiums on the dialogue of the Abrahamic faiths. Their numerous intellectual and academic achievements, including Isma‘il al Faruqi’s pivotal role in the founding and empowerment of the IIIT, deserve far more coverage than that provided by this cursory review. But the experiences and insights as well as the team spirit they developed over the years, and through a great deal of globe-trotting, were to stand them in good stead as they approached a task of encyclopedic proportions. Indeed, any glimpse into the features of Atlas, one ...